Peculiarities of normative and legal regulation for the activity of higher education institutions with specific conditions which provide training for the National Police of Ukraine - D. V. Shvets (Law and Safety)
The peculiarities of normative and legal regulation for the activity of higher education institutions with specific conditions which provide training for the police have been analyzed. It has been established that such normative legal regulation is implemented by a considerable number of acts of national legislation which, taken together, can be described as a system comprising the Constitution of Ukraine and international treaties of Ukraine, Laws of Ukraine, decrees of the President of Ukraine, resolutions of the Cabinet of Ministers of Ukraine, orders of the Ministry of National Defence and orders of the Ministry of Internal Affairs. The general significance of the legal regulations governing such institutions of higher education has been elucidated and the role of individual legislation in this area has also been established. It has been substantiated that the normative and legal regulation of this sphere of social relations is being implemented in several directions: defining the general legal basis for the activities of institutions of higher education with specific teaching conditions, establishing the legal status of the subjects of these social relations and defining specific aspects of the implementation of the educational process. It has been noted that one of the main features of the legal regulation of higher education institutions with specific learning conditions is their management by several central executive bodies. Emphasis has been placed on the expediency of reducing the regulatory impact on public relations regarding the activities of higher education institutions with specific training conditions that provide training for bodies and units of the National Police of Ukraine by by-laws of national legislation. It has been determined that this need is due to the fact that a significant number of by-laws are extremely outdated and can not take into account all current trends in higher education institutions with specific training conditions that provide training for bodies and units of the National Police of Ukraine. It has been proved that the systematization of national legislation in this area will have a positive effect on the activities of both the National Police of Ukraine as a whole and higher education institutions with specific training conditions that train for it.